Evaluating healthcare professionals’ readiness for community-based kangaroo mother care in resource-limited setting - Hagos T. Atalay; Victoria J. Kain; Amanda G. Carter (PLoS ONE, 2026)
Background Neonatal mortality remains a major public health challenge in low-resource settings. Community-Based Kangaroo Mother Care (cKMC) improves survival outcomes for preterm and low-birthweight infants. However, its implementation is hindered by healthcare professionals’ readiness and the lack of validated tools to assess and support cKMC. This study primarily aimed to assess the readiness of healthcare professionals for the implementation of cKMC. In addition, this study developed and performed preliminary validation of an instrument to measure healthcare professionals’ capability, perception, knowledge, and engagement with cKMC. Methods A cross-sectional study was conducted among 593 healthcare professionals in northern Ethiopia. A 30-item instrument was developed through literature review, expert consultation, and cognitive interviews. Preliminary psychometric evaluation included content validity, internal consistency reliability, and construct validity testing. Sampling adequacy was confirmed using the Kaiser–Meyer–Olkin measure of 0.82 and Bartlett’s test of sphericity (P < 0.001). Descriptive analyses, Kruskal–Wallis tests, and generalised linear models were applied to examine subscales of readiness and their predictors. Results The survey instrument assessing healthcare professionals’ capability, perception, knowledge, and engagement regarding cKMC demonstrated strong psychometric performance (CVI = 0.97; Cronbach’s α = 0.85). An evaluation of construct validity through factor analysis generated four factors: capability, perception, knowledge, and engagement. Total and subscale scores correlated significantly. Only 13.2% of participants had read the national the cKMC guideline, and 73.7% had not received formal training; 55.6% reported inadequate workplace support. In multivariable analyses, prior cKMC experience predicted higher perception scores (p = .029); age predicted knowledge (p < .001); and both age and work experience were associated with higher engagement (p < .001). Conclusion The instrument demonstrated satisfactory preliminary reliability and construct validity, providing a context-appropriate measure of healthcare professionals’ readiness to implement cKMC. Although perceptions were positive, substantial gaps in knowledge, familiarity with guidelines, and practical capabilities highlight the need for structured training and institutional support to enhance community-based neonatal care.